2013
DOI: 10.1128/genomea.00218-12
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of Avirulent Riemerella anatipestifer Strain RA-SG

Abstract: Riemerella anatipestifer is a pathogenic bacterium that has spread all over the world and is associated with epizootic infections in waterfowl and other avian species. R. anatipestifer RA-SG is an avirulent strain, isolated from an infected duck in Guangdong province, China. The genome sequence of this species is presented herein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Among the known serotypes of R. anatipestifer, there are huge variations in the virulence between serotypes and between different strains even within the same serotype (Subramaniam et al, 2000). Although four genome sequences of R. anatipestifer of strains ATCC 11845 (Mavromatis et al, 2011), RA-GD (Yuan et al, 2011), RA-YM (Zhou et al, 2010), and RA-SG (Yuan et al, 2013) have been reported, little is known about the molecular basis of the pathogenicity of R. anatipestifer infection, and so far, few virulence factors have been characterized other than virulence-associated protein D (VapD) (Chang et al, 1998), CAMP cohemolysin (Crasta et al, 2002), and outer membrane protein A (OmpA) (Hu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Among the known serotypes of R. anatipestifer, there are huge variations in the virulence between serotypes and between different strains even within the same serotype (Subramaniam et al, 2000). Although four genome sequences of R. anatipestifer of strains ATCC 11845 (Mavromatis et al, 2011), RA-GD (Yuan et al, 2011), RA-YM (Zhou et al, 2010), and RA-SG (Yuan et al, 2013) have been reported, little is known about the molecular basis of the pathogenicity of R. anatipestifer infection, and so far, few virulence factors have been characterized other than virulence-associated protein D (VapD) (Chang et al, 1998), CAMP cohemolysin (Crasta et al, 2002), and outer membrane protein A (OmpA) (Hu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Three genomic sequences of R. anatipestifer , published (Yuan et al, 2011) or available as database entries (GenBank accession numbers CP003787 and CP004020), also carry chromosomally encoded genes similar to tet (X) (Figure 1). Interestingly, four other strains of R. anatipestifer , for which genome sequences are available (Mavromatis et al, 2011; Zhou et al, 2011; Wang et al, 2012; Yuan et al, 2013), have not yet acquired tet (X). No information regarding antibiotic use practices at sampling sites where R. anatipestifer strains have been isolated is available in the cited publications.…”
mentioning
confidence: 99%
“…A total of 4,199 bp containing 61 repeat sequences were detected in the genome. Similar to another avirulent R. anatipestifer , RA-SG, two credible clustered regularly interspaced short palindromic repeats (CRISPRs) and two possible CRISPRs were found ( 14 ). In addition, there is an 89-bp prophage sequence.…”
Section: Genome Announcementmentioning
confidence: 90%